A novel case of renal pathergy reaction in a Behçet's disease patient complicated by IgA vasculitis. Issue 1 (December 2017) - Higashihara, Takaaki; Okada, Akira; Kusano, Taiko; Ishigaki, Kazuyoshi; Shimizu, Akira; Takano, Hideki
Abstract Background A pathergy reaction is defined as a hyperreactivity of the skin in response to minimal trauma, which is important in the diagnosis of Behçet's disease (BD). However, a pathergy reaction may not be restricted to the skin, and little is known about whether an invasive medical procedure can induce the reaction. Here we present a pathergy reaction induced by renal biopsy, an invasive procedure. Case presentation A 46-year-old man who was diagnosed with IgA vasculitis (IgAV) at the age of 38 was treated with prednisolone and mizoribine. However, complications such as common carotid arteritis or recurrent oral ulcer suggested the possibility of another pathophysiology. Later, increasing urine protein developed, suggesting disease aggravation. However, renal biopsy showed arteriosclerotic changes caused mainly by hypertension, negating exacerbation. After renal biopsy, his renal dysfunction and body temperature fluctuated, and detailed examinations revealed recurrent oral and genital ulcers and a folliculitis-like rash on his scrotum. Later, he complained of myodesopsia caused by hemorrhage in the ocular fundus due to occlusive vasculitis. Complete BD was diagnosed after development of the symptoms, and he was treated with prednisolone and colchicine. Conclusion Co-occurrence of BD with IgAV is very rare and may be associated with immune disorders. Interestingly, a renal biopsy revealed BD, which was masked by the presence of IgAV, and elucidated the etiology of the unexplainable symptoms. To the best of our knowledge, this is the first report of renal pathergy. This case enlightens clinicians to the fact that not only a needle stimulation but also an invasive procedure can cause a pathergy reaction.